Analisis Risiko Pembangunan Jalan Tol Pekanbaru - Dumai Pada Tahap Konstruksi (Studi Kasus Jalan Tol Pekanbaru - Dumai) - Zulfiqar, Muhammad; Sandhyavitri, Ari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Pekanbaru-Dumai highway is now an important highway, the condition of the existing road are consist of 2-lane road 2-way, predictable way Pekanbaru-Dumai will experience overcapacity in Kandis-Dumai section in 2015. To overcome this situation the toll road is planned. The investment of highway construction will always be involved in risk with certain scale, it is necessary to do the risk analysis. The purpose of this study is to identify and analyze the risk, measuring of risk probability point and risk impact and risk test by performing simulations using @Risk For Excel software. This research was conducted using a survey method and interview with respondents. The survey was conducted in three phases, namely: beginning survey, preliminary survey and detailed survey. Based on research conducted identified four risk factors are financing risk, construction risk, equipment risk and force majeure. These four risks are identified in the medium risk category. The influence level of risk impact to the increase of construction investment budget plan Pekanbaru-Dumai toll roads as a whole amounted to 8.07% (Rp. 1,183 trillion) with risk factor for 0,549 then classified as medium risk. While detaily 15% (Rp. 2,194 trillion) by a factor of 0.685 then risk being classified as at risk. The most sensitive risk is the risk of development. Keywords: Risk Analysis, Impact, Pekanbaru-Dumai, Toll Road, Probability